Response of the oxygen uptake efficiency slope to exercise training in patients with chronic kidney disease - Thomas J. Wilkinson; Emma L. Watson; Noemi Vadaszy; Luke A. Baker; João L. Viana; Alice C. Smith (The Korean Society of Nephrology, 2020)
Background : : Chronic kidney disease (CKD) patients have poor cardiorespiratory fitness. Although cardiopulmonary exercise testing (CPET) is a universal assessment of cardiorespiratory fitness, values taken at 'peak' effort are strongly influenced by motivation and the choice of test endpoint. The oxygen uptake efficiency slope (OUES) integrates cardiovascular, musculoskeletal, and respiratory function into a single index to provide a more pragmatic and safer alternative to maximal testing. No research has explored whether exercise can improve the OUES in CKD patients. Methods : : Thirty-two patients with non-dialysis CKD were recruited into a 12-week exercise program consisting of mixed aerobic and resistance training three times a week. CPET was conducted at baseline, and then, following a 6-week control period, at pre- and post-exercise intervention. Direct measurements of oxygen consumption (V̇O2) and ventilatory parameters were collected. The OUES was calculated as the relationship between V̇O2 and the log10 of minute ventilation (V̇E). Results : : No changes were observed in any variable during the control period, although modest increases in V̇O2peak were observed. No meaningful changes were observed as a result of exercise in any cardiorespiratory value obtained. The OUES calculated at 100%, 90%, 75%, and 50% of exercise duration did not change significantly after 12 weeks of exercise training. Conclusion : : Our results show that 12 weeks of exercise training had no beneficial effects on the OUES, which supports the modest change observed in V̇O2peak. The lack of change in the OUES and other parameters could indicate a dysfunctional cardiorespiratory response to exercise in patients with CKD, likely mediated by dysfunctional peripheral metabolic mechanisms.